Comparison Between Kidney and Liver Transplant Recipients Admitted to a Referral Center Regarding Coronavirus-2019 Manifestations in the Northeast of Iran During Three Peaks of Pandemic - Aliakbarian, Mohsen; Khodashahi, Rozita; Sabbagh, Mahin G.; Naderi, Hamid Reza; Khodashahi, Mandana; Jahanian, Shahrzad; Moghaddam, Maliheh Dadgar (Current Respiratory Medicine Reviews, 2021)
Background: Transplant recipients are at high risk for severe Coronavirus disease-2019 (COVID-19). Transplant recipients are immune-compromised individuals at high risk for severe infection. This study aimed to compare the presentations and outcomes of liver and kidney transplant recipients who were infected with COVID-19 in the Iranian population. Methods: This cross-sectional study was conducted at Imam Reza and Montaserieh Hospitals affiliated with Mashhad University of Medical Sciences, Mashhad, Iran, between 2020 and 2021. In general, 52 patients were selected and divided into two groups of the kidney (n=28) and liver (n=24) transplantation. Two groups were compared in terms of demographic characteristics and clinical findings. Results: Of the 52 patients, severe COVID-19 infection was reported in 61% of the patients. There was no significant difference between the two groups in terms of symptoms, except for cough (χ2=8.09; P=0.004), clinical condition, and laboratory symptoms, except for creatinine (Z=14; P<0.005), alkaline phosphatase (Z=4.55; P=0.03), total bilirubin (Z=8.93; P=0.03), and partial thromboplastin time (Z=5.97; P=0.01). There was no relationship between the outcome and the use of immunosuppressive medications (P>0.05). All patients with kidney transplantation survived, while two cases in the liver transplantation group failed to survive (χ2=2.42; P=0.11). Conclusion: The mortality rate was higher in the liver transplant recipients, compared to the patients who underwent kidney transplantation.
Keywords: immunosuppressive